La Responsabilité Sociétale De L’entreprise : Les Différentes Approches Conceptuelles - Dinia, Jihane; Chakor, Abdellatif (European Scientific Journal, ESJ, 2018)
What are we talking about when we refer to the concept of Corporate Social Responsibility (CSR)? Behind every word that constitutes "CSR" lie great debates, starting with its definition. The purpose of our article is to emphasize the issue of the CSR through a brief genealogical overview and the confrontation of several definitions based on an academic literature review. Our study revealed a proliferation of proposed definitions of the concept, reflecting different approaches, which certainly enriched the debate, but complicated the subject. Therefore, after 50 years of research, CSR remains a very subjective concept, which is not yet complete..